Processing Gaze Responses to Dynamic 2D Stimuli - Špakov, O.; Miniotas, D. (Elektronika ir Elektrotechnika, 2008)
Huge amount of data collected in experiments on gaze behavior requires efficient tools for analysis and visualization of the data to facilitate its interpretation. Although there are a number of tools available today that support observations of static 2D stimuli, the handling of dynamic stimuli remains a major challenge. The traditional approach analyzes the data frame-by-frame, which is very tedious and time consuming. We propose a simplified and intuitive way to visualize gaze responses to dynamic 2D stimuli. Graphical user interfaces are presented in detail along with comprehensive explanations how to take the best advantage of the functionality provided by the built-in analysis and visualization tools. Ill. 8, bibl. 6 (in English; summaries in English, Russian and Lithuanian).